Assessments of Intestinal and Hepato Toxicity in Sprague Dawley Rats Induced by Clopidogrel - Siddique, Abu Bakar; Abid, Uriba; Ashraf, Usman; Sadaf, Kashifa; Sajid, Abdul Qadeer; Rana, Poonum; Altaf, Hafza (American Journal of Biology and Natural Sciences, 2025)
Clopidogrel, a widely used antiplatelet drug, is associated with gastrointestinal adverse effects, though its direct toxic impact on the intestine and liver remains inadequately characterized. This study investigated the potential intestinal and hepatotoxic effects of clopidogrel in a rat model. Male Sprague Dawley rats were administered clopidogrel (10 mg/kg/day, orally) or vehicle for 14 days. Clopidogrel treatment induced significant macroscopic and histological intestinal damage, evidenced by ulcers, hemorrhagic lesions, blunted villi, and inflammatory cell infiltration. This injury was mechanistically linked to a significant increase in myeloperoxidase activity and malondialdehyde levels, indicating neutrophil infiltration and oxidative stress, alongside a downregulation of tight junction proteins (ZO-1, Occludin), suggesting barrier integrity compromise. Concurrently, clopidogrel caused dose-dependent hepatotoxicity, marked by elevated serum ALT, AST, and ALP levels, and histopathological evidence of necrosis and inflammation. Hepatic injury was driven by oxidative stress, demonstrated by increased MDA and depleted glutathione, and a heightened inflammatory response with elevated TNF-α and IL-6. These findings demonstrate that clopidogrel induces significant intestinal and hepatic damage through mechanisms involving oxidative stress, inflammation, and loss of barrier function, highlighting a need for monitoring these toxicities in clinical practice.